Expedient synthesis of highly substituted 3, 4-dihydro-1, 2-oxathiine 2, 2-dioxides and 1, 2-oxathiine 2, 2-dioxides: revisiting sulfene additions to enaminoketones. Issue 44 (6th November 2019) - Aiken, Stuart; Anozie, Kelechi; de Azevedo, Orlando D. C. C.; Cowen, Lewis; Edgar, Ross J. L.; Gabbutt, Christopher D.; Heron, B. Mark; Lawrence, Philippa A.; Mills, Abby J.; Rice, Craig R.; Urquhart, Mike W. J.; Zonidis, Dimitrios
Abstract : The addition of sulfenes to substituted enaminoketones, followed by a facile Cope elimination, provides efficient access to a diverse series of 1, 2-oxathiine 2, 2-dioxides. Abstract : Diversely substituted 1, 2-oxathiine 2, 2-dioxides, including 3, 5, 6-triaryl-, 3, 6-diaryl-, 3, 5-diaryl-, 5, 6-diaryl- and selected fused heterocyclic analogues, have been efficiently obtained by the application of a mild Cope elimination of a 4-amino moiety from the requisite 4-amino-3, 4-dihydro-1, 2-oxathiine 2, 2-dioxides, which themselves were readily obtained by the addition of sulfenes to enaminoketones.